Local perception scale on ecotourism impacts and quality of life - Adam, Syamimi; Shuib, Ahmad; Ramachandran, Sridar; Kunasekaran, Puvaneswaran; Mohammad Afandi, Syamsul Herman; Engku Hassan, Engku Nor Kamilah (IDOSI Publications, 2018)
The purpose of this paper is to develop a scale to determine the locals’ perception on impacts and quality of life in an ecotourism destination. This paper presents the findings and development of main factors determining locals’ perception on the ecotourism industry and quality of life in Tasik Kenyir, Malaysia. The variables from previous study of local communities’ impacts were combined with new found factors through an initial exploratory investigation to produce a new measurement scale. This combination of existing and new variables provided the important steps to develop the scale. Factor analysis was used as the tool in the reduction method. The significant variables found were extracted and regrouped according to the suitable factors in generating the new scale. As a result, 29 items were identified to have significant contribution in determining locals’ perception on ecotourism that was regrouped into 8 factors. This finding can be used in determining locals’ perception on ecotourism impacts and quality of life. The scale on locals’ perception on ecotourism impacts and quality of life also would be important to contribute policy makers to review and evaluate Malaysia’s plans and policies working towards ecotourism development strategy in future.